2018
DOI: 10.1159/000491397
|View full text |Cite
|
Sign up to set email alerts
|

11β-Hydroxysteroid Dehydrogenase Type 1 Inhibitor Development by Lentiviral Screening Based on Computational Modeling

Abstract: In this study, rat and human 11β-hydroxysteroid dehydrogenase type 1 (11β-HSD1) have been cloned by lentiviral transduction and expressed by CHO-K1 cells. The results showed that recombinant plasmids contained R11bhsd1 or H11bhsd1 have been constructed, which is consistent with the gene bank respectively. A clone cell was selected with G418 and cultivated to express 11β-HSD1. 11β-HSD1 catalytic activity of rat and human were 99.5 and 98.7%, respectively, determined by scanning radiometer. And the cloned CHO-K1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The solution of lentivirus was centrifuged (500× g for 10 min), to remove the cellular debris and purify the lentivirus. The administered virus titer was 10 7 [ 18 ]. The tail veins of 16 mice were injected with lentivirus solution, containing pLVX-EF1α-IRES-ZS green plasmid, and the other half were injected with pLVX-11β-HSD1 green plasmid every 3 days, for 6 consecutive injections of 500 μL.…”
Section: Methodsmentioning
confidence: 99%
“…The solution of lentivirus was centrifuged (500× g for 10 min), to remove the cellular debris and purify the lentivirus. The administered virus titer was 10 7 [ 18 ]. The tail veins of 16 mice were injected with lentivirus solution, containing pLVX-EF1α-IRES-ZS green plasmid, and the other half were injected with pLVX-11β-HSD1 green plasmid every 3 days, for 6 consecutive injections of 500 μL.…”
Section: Methodsmentioning
confidence: 99%
“…GetBox Plugin, a plugin of PyMOL 2.4 software, was used to obtain the active site for molecular docking. LeDock 1.0 software (version 1.0, http://lephar.com ) was used for molecular docking ( Liu et al, 2018 ). The binding pocket was set at 3.9, 25.0, 15.9, 31.6, 22.2, and 38.7, and the remaining parameters as default.…”
Section: Methodsmentioning
confidence: 99%
“…In previous studies, we found that H8 reduced the effect of reducing blood glucose concentration and effectively improved insulin sensitivity in T2D mice, and the effect was better than that of curcumin. 41 , 42 In this study, NVs were used as a sustained-release agent to encapsulate H8, and more biologically targeted nanodrugs (H8-BMSCS-NVS) were prepared by taking advantage of the fact that it takes a long time for molecules to enter and exit the NVs. Our results demonstrated that H8-BMSCs-NVs effectively improved insulin resistance, inhibited hepatic steatosis, and restored impaired liver function in T2D mice.…”
Section: Discussionmentioning
confidence: 99%